2021
DOI: 10.1080/09687637.2021.1943315
|View full text |Cite
|
Sign up to set email alerts
|

Exploring essential components of addiction recovery: a qualitative study across assisted and unassisted recovery pathways

Abstract: Even though various pathways to addiction recovery have been identified, knowledge on overarching essential components of addiction recovery processes remains limited. To explore these essential components, in-depth interviews were conducted with a heterogeneous group of individuals across pathways to addiction recovery (i.e. a low-threshold activation center, Narcotics Anonymous, a CRA þ vouchers out-patient program, residential treatment programs, and 'natural' recovery). The interviews (n ¼ 25) were audio-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 63 publications
(99 reference statements)
1
7
0
Order By: Relevance
“…Although families have been identified as a primary context of care for young adults' substance use treatment processes (129), this study showed that the family context among adult children of parents with SUDs is often not facilitative for their treatment and recovery processes. In line with evidence on the importance of relationships and social resources needed for initiation and maintenance of addiction recovery (130)(131)(132)(133)(134)(135)(136)(137), this study confirms the importance of interpersonal relationships and social resources in readiness to change and early stages of recovery (131,(138)(139)(140)(141)(142)(143). Although the importance of social networks in improving early and more sustained recovery outcomes has been established (144), this study provides insight in how family, parent and peer support systems can both inhibit and encourage recovery in offspring of parents with SUDs.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although families have been identified as a primary context of care for young adults' substance use treatment processes (129), this study showed that the family context among adult children of parents with SUDs is often not facilitative for their treatment and recovery processes. In line with evidence on the importance of relationships and social resources needed for initiation and maintenance of addiction recovery (130)(131)(132)(133)(134)(135)(136)(137), this study confirms the importance of interpersonal relationships and social resources in readiness to change and early stages of recovery (131,(138)(139)(140)(141)(142)(143). Although the importance of social networks in improving early and more sustained recovery outcomes has been established (144), this study provides insight in how family, parent and peer support systems can both inhibit and encourage recovery in offspring of parents with SUDs.…”
Section: Discussionsupporting
confidence: 82%
“…Activating non-substance using family and friends has shown to provide potential pathways to help persons with SUDs access and benefit from community support (154,155). Moreover, given that early recovery stages are sensitive periods for experiencing loneliness and social isolation (138), which has been associated with SUDs (156)(157)(158), adult offspring with SUDs may benefit from strategies to build and sustain prosocial connections and recovery-supportive networks (159), that prepare them for "normal everyday living" (137) and "outside living" in a way that promotes positive relational enactment.…”
Section: Discussionmentioning
confidence: 99%
“…All other papers in this special issue (Anderson et al, 2021;Dekkers et al, 2021;Frings et al, 2021;Gueta et al, 2020;Jason et al, 2021) focus on diverse recovery mediators and mechanisms and their role in individuals' recovery trajectories, reflecting the primary objective of the REC-PATH study.…”
Section: Mechanisms and Mediators Of Addiction Recoverymentioning
confidence: 99%
“…Developing 'the self' and a 'post-addiction' identity as well as social identification appear to be crucial elements in early recovery (Frings et al, 2021;Kougiali et al, 2021;Van Steenberghe et al, 2021). Second, time in recovery and recovery stage came to the fore as important predictors of stability of behaviour change (Dekkers et al, 2021;von Greiff & Skogens, 2021). Third, Cloud and Granfield's notion of recovery capital (Cloud and Granfield 2008) emerged in several papers, illustrating the importance of personal, social and community resources for promoting recovery and avoiding relapse.…”
Section: Mechanisms and Mediators Of Addiction Recoverymentioning
confidence: 99%
See 1 more Smart Citation